2016
DOI: 10.1590/0103-6440201600672
|View full text |Cite
|
Sign up to set email alerts
|

Dentifrice Containing Extract of Rosmarinus officinalis Linn.: An Antimicrobial Evaluation

Abstract: This study aimed to evaluate the antimicrobial activity of a dentifrice containing an alcoholic extract of rosemary on oral bacteria, compared to a commercially available herbal dentifrice. Standard strains of Streptococcus mutans (ATCC 25175), Streptococcus oralis (ATCC 9811) and Lactobacillus rhamnosus (ATCC 7469) were used, as well as different toothpastes based on rosemary (TR), on propolis (TH), triclosan (positive control) (TPC) and non-fluoridated dentifrice (negative control) (TNC). Bacteria were seede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
4

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
1
11
0
4
Order By: Relevance
“…The new tissues formed inside the root canal showed characteristics similar to the cementum, bone, and periodontal ligament 14 Valones et al [24] The present study demonstrated that a dentifrice containing exclusively rosemary extract has the capability of inhibiting the growth of the studied bacteria. However, for the inhibition of L. rhamnosus, a propolis-based commercial dentifrice was more effective than the dentifrice containing rosemary extract 15 De Luca et al [25] All rats gained weight and remained apparently healthy and active throughout the experiment.…”
Section: N°bibliographic Referencesupporting
confidence: 58%
See 1 more Smart Citation
“…The new tissues formed inside the root canal showed characteristics similar to the cementum, bone, and periodontal ligament 14 Valones et al [24] The present study demonstrated that a dentifrice containing exclusively rosemary extract has the capability of inhibiting the growth of the studied bacteria. However, for the inhibition of L. rhamnosus, a propolis-based commercial dentifrice was more effective than the dentifrice containing rosemary extract 15 De Luca et al [25] All rats gained weight and remained apparently healthy and active throughout the experiment.…”
Section: N°bibliographic Referencesupporting
confidence: 58%
“…The most toxic signals in subacute studies were observed in males at a dose of 200 mg/kg HERP. These results suggest estrogen-like activity, possibly from the isoflavones in HERP 24 Rodrigues et al [34] The results of the analyses show the main components (inorganic and organic components) of the "caba-leão" wasp nests (Sceliphron sp., Sphecidae) used by "caboclos" as a topical medication to treat mumps and earaches. The ethnopharmacological data collection consisted of samples of wasp nests and soil, as a source of inorganic elements, from the Jaú and Unini Rivers, in the River Negro basin, Amazon, Brazil.…”
Section: N°bibliographic Referencementioning
confidence: 95%
“…Antimicrobial activity of R. officinalis L. propylene glycol extract showed a significant reduction in colony forming units per mililiter (CFU/ml) in all biofilms at MIC of 200 mg/ml (23,30). Also, some studies revealed that dentifrice containing alcoholic R. officinalis extract had antimicrobial activity similar to commercially available herbal dentifrice against some streptococci (32).…”
Section: Resultsmentioning
confidence: 95%
“…Results in previous studies in which methanolic extracts and aqueous extracts of T. vulgaris showed no effect either on S. mutans or S. sanguinis (4) could The present study showed an inhibitory concentration of S. officinalis at 37.5 µg/ml for S. mutans. Moreover, significant reduction in the S. mutans colony count has been recorded in vivo evaluations as well as in the agar diffusion method (7,32,17).…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, foi constatado também atividade antimicrobiana na pesquisa processada por Valones et al 29 cujo objetivo foi avaliar a atividade antimicrobiana de um dentifrício à base de extrato alcoólico de Alecrim sobre bactérias orais como Streptococcus mutans, Streptococcus oralis e Lactobacillus rhamnosus, comparando-o a um dentifrício herbal disponível no mercado. O dentifrício contendo extrato de alecrim foi capaz de inibir o crescimento de S. mutans, S. oralis e L. rhamnosus, revelando uma atividade antimicrobiana semelhante ao dentifrício disponível comercialmente na inibição de S. mutans e S. oralis.…”
Section: O Constituintes Químicos Rosmarinus Officinalis Lunclassified